Soluble CD72, is a T-cell activator probably via binding to CD6 in homeostasis and autoimmunity - Eiza, Nasren; Sabag, Adi; Kessler, Ofra; Toubi, Elias; Vadasz, Zahava (Frontiers in Immunology, 2024)
Background: CD72 is a highly required regulatory molecule in B cells. Its sufficient expression is crucial for maintaining self-tolerance. In contrast, soluble CD72 (sCD72) is reported to be increased in the serum of autoimmune diseases such as systemic lupus erythematosus and primary Sjogren's syndrome (pSS). Objective: We wanted to assess the biological effect of sCD72 on CD4+T cells. Methods: We performed mass spectrometry and co-immunoprecipitation experiments to look for a sCD72 receptor on activated CD4+T cells. Afterward, to explore the biological functions of sCD72, we used flow cytometry for the cytokine secretion profile, a phosphorylation assay for the signaling pathway, and a CFSE dye-based assay for cell proliferation. Results: We found and validated the sCD72 and CD6 interaction as a possible ligand-receptor interaction. We also demonstrated that sCD72 significantly increases the expression of pro-inflammatory cytokines, namely IL-17A and IFN-γ, in activated CD4+T cells and increases the proliferation of CD4+T cells, possibly through its activation of the SLP-76-AKT-mTOR pathway. Conclusion: The sCD72-CD6 axis on activated CD4+T cells is probably a new signaling pathway in the induction of immune-mediated diseases. Therefore, targeting sCD72 may become a valuable therapeutic tool in some autoimmune disorders.